Raw Multi-Channel Seismic Shot Data from the Bering Shelf and Chukchi Sea acquired during R/V Maurice Ewing expedition EW9410 (1994) ... - Klemperer, Simon (Interdisciplinary Earth Data Alliance (IEDA), 2006)
This data set was acquired with the LDEO Multi-Channel Seismic system during R/V Maurice Ewing expedition EW9410 conducted in 1994 (Chief Scientist: Dr. Simon Klemperer). These data files are of SEGY format and include Multi-Channel Reflection Seismic shot data that have not been processed. Data were acquired as part of the project: Crustal Evolution of the Bering Shelf-Chukchi Sea, and funding was provided by NSF grants: EAR93-16573, EAR93-17087, EAR93-17142, EAR93-17531, and USGS-XXX. These data are cited by Klemperer et al., 2002, Wolf et al., 2002, Sherwood et al., 2002, Grantz et al., 2002, and Miller et al., 2002. ...